PEMANFAATAN TEKNOLOGI DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI SD NEGERI 7 METRO UTARA - Masitoh, Isti; Selviani, Tina; Jihan Firliani, Wini; Putri Ramadani, Fauzya; Nuryasir, Ahmat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The use of technology in education has become one of the efforts to improve the quality of learning in elementary schools. This study aims to describe the utilization of technology in improving the quality of learning at SD Negeri 7 Metro Utara, covering the forms of technology use, the school's efforts in supporting its implementation, its impact on learning quality, and the challenges faced along with the solutions applied. This study used a qualitative approach with a descriptive method. Data were obtained through observation, interviews, and documentation, with informants consisting of the school principal, a teacher, and students. Data were analyzed using the Miles and Huberman model, covering data reduction, data display, and conclusion drawing, while data validity was tested through source and technique triangulation. The results show that technology has been used in the learning process through projectors, laptops, panel TVs, learning videos, YouTube, Canva, and Artificial Intelligence (AI) as supporting media. The school supports this through providing facilities, organizing In House Training (IHT), and giving teachers opportunities to join competency development activities. The use of technology brings positive impacts, including increasing students' motivation and engagement, easing teachers in delivering material, and helping students understand material through visual and audiovisual media. However, implementation still faces challenges such as limited budget, an inadequate number of devices, and damaged facilities, which are addressed through regulating facility use, device maintenance, and continuous teacher training. Overall, the use of technology contributes positively to the quality of learning, especially when supported by adequate facilities and teachers' competence in integrating technology into the learning process.